Performance Analysis of Receiving Staff in the Accounting Department at Manhattan Hotel Jakarta - Menajang, Brenda Anastasya Hariet; Warokka, Margaretha N.; Kalele, Selvi; Djamali, Radjab (Journal of Multi-Disciplines Science, 2024)
Hotels provide food and beverage accommodation services and other service facilities intended for the public. The Accounting Department has a vital role in making and receiving reports. This research analyses the performance of receiving employees in the Accounting Department at Manhattan Hotel Jakarta. This study uses a qualitative method. Data was collected using interviews, observation and literature study. This research indicates that employee performance in the employee quality dimension still needs to be of better quality. Furthermore, from the experience dimension, employees need to improve and develop their work performance. Employees in the Accounting Department need to increase their accuracy in receiving goods. Hotel management needs to supervise employees to improve their performance.